First Neonatal Demise with Travel-Associated Zika Virus Infection in the United States of America - Nikolaos Zacharias; Janice Whitty; Sarah Noblin; Sophia Tsakiri; Jose Garcia; Michael Covinsky; Meenakshi Bhattacharjee; David Saulino; Nina Tatevian; Sean Blackwell (Thieme Medical Publishers, Inc., 2017)
Zika virus is increasingly recognized as a fetal pathogen worldwide. We describe the first case of neonatal demise with travel-associated Zika virus infection in the United States of America, including a novel prenatal ultrasound finding. A young Latina presented to our health care system in Southeast Texas for prenatal care at 23 weeks of gestation. Fetal Dandy-Walker malformation, asymmetric cerebral ventriculomegaly, single umbilical artery, hypoechoic fetal knee, dorsal foot edema, and mild polyhydramnios were noted upon initial screening prenatal sonography at 26 weeks. A growth-restricted, microcephalic, and arthrogrypotic infant was delivered alive at 36 weeks but died within an hour despite resuscitation. The neonatal karyotype was normal. Flavivirus IgM antibodies were identified in the serum of the puerpera, once she disclosed that she had traveled from El Salvador to Texas in the early second trimester. Zika virus was identified in the umbilical cord and neonatal brain. Fetal arthritis may precede congenital arthrogryposis in cases of Zika virus infection and may be detectable by prenatal sonography. Physician and health care system vigilance is required to optimally address the significant and enduring Zika virus global health threat.